A historic ruin – interventions and their conditions - Molski, Piotr (Protection of Cultural Heritage, 2020)
The effective protection of historical ruins, just as of other monuments, depends on their contemporary use. Adaptation of ruins to utilitarian standards requires preventive and preservative conservation, but also architectural interventions necessary for new functions. The principles of dealing with ruins were included in the Charter of Historical Ruins adopted by Polish National Committee ICOMOS in 2012. The characteristics of objects known to the conservation and architectural community, carried out against the background of the Charter, allowed to distinguish, apart from the traditional methods of preventive conservation, four types of intervention consisting in the introduction of additions to the historic ruins, in different scope and scale –ranging from the filling of defects to consolidate the destructed walls, through addition of "small architecture" items, to utility objects and cubic additions in the place of the unpreserved fragments of the original mass of the building. Evaluation of the intervention methods allows to define their conditions and to confront them with recommendations of the Charter of Historical Ruins. The confrontation of the Charter's recommendations with examples of transformations of selected objects confirms the accuracy of the Charter's provisions and their usefulness in the conservator's assessment of the transformation of ruins and preservation of their historic values. The interventions which enable the use of ruins are in accordance with social expectations and the aspirations of their owners, and most importantly, they significantly increase the chances of restoration protecting the ruins from destruction.